Effect Sourdough from Snake Fruit (Salacca zalacca) on Microbiota and Texture of Rice Flour Bread - Nia Agustina; Rini Yanti; Dian Anggraini Suroto (Jurnal Teknologi Hasil Pertanian, 2025)
The use of fruit in the manufacture of sourdough provides nutrients and substrates that can improve the microbiota in sourdough and affect the characteristics of sourdough bread. The study aimed to determine the differences in the characteristics of the snake fruit sourdough microbiota on the effect of the texture of rice flour white bread. The snake fruit is peeled and cut to be fermented for several days, then the water from the snake fruit fermentation is mixed with flour to be fermented into the sourdough. Furthermore, it is applied to make plain bread with rice flour as a leavening agent. The results showed that the snake fruit starter had a LAB of 8.77 Log CFU/g and yeast 7.72 Log CFU/g with a pH of 3.62. Snake fruit sourdough (SDS) has a shorter fermentation time of 3 days to reach ripe sourdough and a pH of 3.25. The amount of Lactic acid bacteria (LAB) and yeast snake fruit sourdough (SDS) was higher than control sourdough (SDF) as follows BAL SDS 9.19 log cfu/g and Yeast SDS 9.42 log cfu/g while LAB SDF 9.03 Log CFU/g and Yeast SDF 9.07 Log CFU/g. The specific volume of SDS is similar to that of commercial SDF and baker's yeast. SDS has a small pore size of 16.29 mm2 so the cells found are higher, namely 6.31 cells/cm2. The use of snake fruit sourdough produced bread with higher hardness, gumminess, and chewiness, but the springiness, cohesivity, and resilience were similar to those of control sourdough bread and commercial yeast bread. In this study, the use of SDS was faster in fermentation time on day 3 SDS had reached its optimal level compared to SDF.